History (Forward N-Gram) or future (Backward N-Gram)? Which model to consider for N-Gram analysis in Bangla? - Khan, Naira; Habib, Md. Tarek; Alam, Md. Jahangir; Rahman, Rajib; UzZaman, Naushad; Khan, Mumit (BRAC University, 2010)
Includes bibliographical references (page 5).